Utilisation of Gas-Phase Ion—Molecule Reactions for Differentiation between Phospho- and Sulfocarbohydrates. Issue 2 (April 2014) - Piatkivskyi, Andrii; Pyatkivskyy, Yuriy; Hurt, Matt; Ryzhov, Victor
Gas-phase ion-molecule reactions of four boron-containing neutrals were explored as a means for differentiation between isobaric phospho- and sulfocarbohydrates. Phosphorylation and sulfation impose an addition of 80 Da to the molecular mass, so for low-resolution mass spectrometers compounds that have such modifications will appear at the same nominal mass-to-charge ( m/z ) ratio. However, the ions of these isobaric species behave differently in ion–molecule reactions. All four evaluated neutral molecules [trimethyl borate (TMB), triethyl borate (TEB), diethylmethoxyborane (DEMB) and diisopropoxymethylborane (DIPMB)] proved to be reactive towards phosphorylated sugars and unreactive towards sulfated carbohydrates. In addition, TMB and TEB were found suitable for distinguishing positional isomers of phosphorylated carbohydrates, while reactions with DEMB and DIPMB were successful in differentiating phosphorylated, sulfated and unmodified deprotonated sugars. Similar reactions in the positive ion mode (alkali cationised) were found to be less conclusive.